The Law of the Land: A Review Article - Weiner, James F. (The Australian journal of anthropology, 2003)
This is a review article of the book Native Title Corporations: A Legal and Anthropological Analysis from the point of view of anthropology. I begin by highlighting the development of Anglo-Australian social anthropology from such figures as Radcliffe-Brown and Fortes, who were heavily influenced by regulatory and normative models from the domain of legal and judicial scholarship and speculate on the contemporary conditions by which this original social anthropological metaphor has apparently achieved a new literalisation. I criticise the legalistic appropriation of anthropological and ethnographic methodology that this book makes explicit, and finally, I express scepticism for the future success of the prescribed body corporate, as described in the Native Title Act (1993), as a model for the possession, transmission and elaboration of indigenous rights to country.